Mast cells protect from post‐traumatic brain inflammation by the mast cell‐specific chymase mouse mast cell protease‐4. Issue 3 (27th November 2012) - Hendrix, Sven; Kramer, Peter; Pehl, Debora; Warnke, Katharina; Boato, Francesco; Nelissen, Sofie; Lemmens, Evi; Pejler, Gunnar; Metz, Martin; Siebenhaar, Frank; Maurer, Marcus
Abstract : Mast cells (MCs) are found abundantly in the brain and the meninges and play a complex role in neuroinflammatory diseases, such as stroke and multiple sclerosis. Here, we show that MC‐deficient Kit W /Kit Wv mice display increased neurodegeneration in the lesion area after brain trauma. Furthermore, MC‐deficient mice display significantly more brain inflammation, namely an increased presence of macrophages/microglia, as well as dramatically increased T‐cell infiltration at days 4 and 14 after injury, combined with increased astrogliosis at day 14 following injury. The number of proliferating Ki67 + macrophages/microglia and astrocytes around the lesion area is more than doubled in these MC‐deficient mice. In parallel, MC‐deficient Kit W‐sh / W‐sh mice display increased presence of macrophages/microglia at day 4, and persistent astrogliosis at day 4 and 14 after brain trauma. Further analysis of mice deficient in one of the most relevant MC proteases, i.e., mouse mast cell protease 4 (mMCP‐4), revealed that astrogliosis and T‐cell infiltration are significantly increased in mMCP‐4‐knockout mice. Finally, treatment with an inhibitor of mMCP‐4 significantly increased macrophage/microglia numbers and astrogliosis. These data suggest that MCs exert protective functions after trauma, at least in part via mMCP‐4, by suppressing exacerbated inflammation via their proteases.—Hendrix, S., Kramer, P., Pehl, D., Warnke, K., Boato, F., Nelissen, S., Lemmens, E., Pejler, G., Metz, M., Siebenhaar, F., Maurer, M. Mast cells protect from post‐traumatic brain inflammation by the mast cell‐specific chymase mouse mast cell protease‐4 . FASEB J. 27, 920–929 (2013). www.fasebj.org